UNCITRAL Receivables Convention: The Possibility for Trans-Tasman Harmonisation - McKinnon, Malcolm (Victoria University of Wellington Law Review, 2003)
This paper examines the UNCITRAL Convention on the Assignment of Receivables in International Trade as it affects New Zealand. The focus of the paper is on the potential effect of the Convention on New Zealand's relationship with Australia. The law in the two countries is very different especially since the passing of New Zealand's Personal Property Securities Act 1999, which is, the author concludes, highly compatible with the UNCITRAL Receivables Convention. The paper considers two sample transactions to illustrate the effects of the Convention in a trans-Tasman context. It concludes that where the Convention (if it enters into force in New Zealand and Australia) applies, there are relatively few complications. Where it does not apply, however, parties to trans-Tasman receivables transactions face complicated applicable law arguments and general uncertainty.